PENYINARAN BERLEBIHAN PADA TAMBALAN RESIN KOMPOSIT DAN AKIBAT YANG DITIMBULKAN - Venita Tanusuwito (Faculty of Dentistry, Universitas Indonesia, 2015)
Dentists are often taught that 'overcure' is better than ' undercure'. Undercure is said to cause serious problem with resin composite fillings. Actually it does not always happen this way. Overcure also has several bad impacts that have never been thought before by practitioners. Researchers claim that curing time informed by resin composite manufacturers is not always correct. Filling material is not the only factor that determines the correct curing time for each filling. Light cure unit performance also plays a major role.